Partisipasi Masyarakat Dalam Pengendalian Vektor Demam Berdarah Dengue (DBD) di Wilayah Kerja Puskesmas Turikale Kabupaten Maros - Vika Yuliandira; Andi Susilawaty; Nurdiyanah Syarifuddin; Syahrul Basri (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2019)
Dengue Haemorrhagic Fever (DHF) is a communicable disease which is caused by a dengue virus transmitted by Aedes aegypti mosquitos. This disease is indicated by symptoms such as sudden high fever around that runs 2-7 days without identifiable warnings, limp, faint, anxiety, heartburn, red spots on skin caused by minor bleed (petechia), and rash (purpura). Vector control, as one of Dengue Haemorrhagic Fever eradication strategies, will be successful with full participation from community members. This research develops a community empowerment program by using Participatory Action Research (PAR) to eradicate Dengue Haemorrhagic Fever. It employs quasi experimental method to examine the issue. the samples consist of 34 respondents who are selected by using total sampling technique and divided into two groups namely intervention group and comparison group. The research findings reveal that the community empowerment program improves community’s knowledge, attitude and action in both groups, as indicated by a paired t test value of = 0.000 in intervention group, and paired t test values of = 0.000 for knowledge, = 0.263 for attitude, and =0.063 for action in the comparison group. The findings also show that the intervention group has successfully decreased more larval density than the comparison group, as indicated by a mean value of ABJ=48% , HI= 47, CI= 11, BI= 70 which is higher than a mean value of ABJ = 20%, HI=21, CI=3 dan BI=21. Therefore, it can be concluded that there is significant difference in the knowledge, attitude, and action of respondents before and after the intervention programs, as signified by the first and second measurement. In conclusion, this research encourages community members to improve their participation in the Dengue Haemorrhagic Fever prevention program held by health centres so that the Dengue Haemorrhagic Fever eradication program can be successful. Keywords: Dengue Haemorrhagic Fever (DHF), participation, PAR theory